Analisis Pengaruh Kebijakan Dividen dan Kinerja Keuangan terhadap Nilai Perusahaan: (Studi pada Perbankan yang terdaftar di BEI pada Tahun 2010-2022) - Noah Gorga Halomoan Gultom; Mahatma Kufepaksi; Muslimin Muslimin (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Firm value is an instrument for investors to consider the success of a company in relation to its share price. The banking industry is one of the most important financial business entities for society because it plays a much needed role in economic and social funding activities. This research aims to examine the influence of dividend policy and financial performance (ROA, LDR and NPL) on the value of companies in the banking sector listed on the BEI in 2010-2022.Testing was carried out using explanatory statistical analysis, data normality testing, and hypothesis testing. The results of this research show that dividend policy (DPR), profitability (ROA), and liquidity (LDR) have a positive effect on company value, while liquidity (LDR) and non-performing loans (NPL) have a negative effect in the banking sector listed on the IDX in 2010 -2022 period.